An optimized culturomics strategy for isolation of human milk microbiota - Wang, Fan; Yu, Lingmin; Ren, Yuting; Zhang, Qianwen; He, Shanshan; Zhao, Minlei; He, Zhili; Gao, Qi; Chen, Jianguo (Frontiers in Microbiology, 2024)
Viable microorganisms and a diverse microbial ecosystem found in human milk play a crucial role in promoting healthy immune system and shaping the microbial community in the infant's gut. Culturomics is a method to obtain a comprehensive repertoire of human milk microbiota. However, culturomics is an onerous procedure, and needs expertise, making it difficult to be widely implemented. Currently, there is no efficient and feasible culturomics method specifically designed for human milk microbiota yet.Therefore, the aim of this study was to develop a more efficient and feasible culturomics method specifically designed for human milk microbiota. We obtained fresh samples of human milk from healthy Chinese mothers and conducted a 27-day enrichment process using blood culture bottles. Bacterial isolates were harvested at different time intervals and cultured on four different types of media. Using matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis, we identified a total of 6601 colonies and successfully obtained 865 strains, representing 4 phyla, 21 genera, and 54 species. By combining CBA and MRS media, we were able to cultivate over 94.4% of bacterial species with high diversity, including species-specific microorganisms. Prolonged pre-incubation in blood culture bottles significantly increased the number of bacterial species by about 33% and improved the isolation efficiency of beneficial bacteria with low abundance in human milk. After optimization, we reduced the pre-incubation time in blood culture bottles and selected optimal picking time-points (0, 3, and 6 days) at 37°C. By testing 6601 colonies using MALDI-TOF MS, we estimated that this new protocol could obtain more than 90% of bacterial species, reducing the workload by 57.0%.In conclusion, our new culturomics strategy, which involves the combination of CBA and MRS media, extended pre-incubation enrichment, and optimized picking time-points, is a feasible method for studying the human milk microbiota. This protocol significantly improves the efficiency of culturomics and allows for the establishment of a comprehensive repertoire of bacterial species and strains in human milk.